Effect of local application of platelet-rich fibrin scaffold loaded with simvastatin on peri-implant bone changes - Sara Fikry El Shafei; Shereen N Raafat; Ayman H Amin; Fardos N Rizk (Wolters Kluwer Medknow Publications, 2022)
Aim: The purpose of this study was to compare the effects of autologous platelet-rich fibrin (PRF) alone and PRF loaded with SIM on peri-implant bone changes and implant stability in patients undergoing implant rehabilitation. Settings and Design: This was a nonrandomized controlled split-mouth study Materials and Methods: The study included 8 males between the ages of 45 and 60 years. Each patient received two implants, one on each side of the arch. One side was treated with PRF alone and the other side with PRF loaded with SIM at the time of osteotomy. A cone-beam computed tomography was used to evaluate bone changes around the insertion of implant sites at 3, 6, and 12 months postoperatively. The secondary outcome included measuring implant stability using Osstell device at baseline and 3 months postinsertion. To compare groups at different time periods, data were examined using a two-way analysis of variance. Statistical Analysis Used: The results were compared between the groups using a two-way analysis of variance, followed by a post hoc Bonferroni test. To examine total bone changes and stability comparisons between the two groups at the end of the trial, an unpaired t-test was utilized Results: The mean crestal bone-level changes in the SIM/PRF group were significantly lower than the PRF group, with a mean shift of 0.9788 ± 0.04853 versus 1.356 ± 0.0434, respectively (P < 0.0001). There was no significant difference between the two groups in implant stability. Conclusion: Peri-implant application of SIM/PRF resulted in less bone changes than PRF alone, which may prove to be beneficial for the long-term success of implants. SIM showed promising results in limiting peri-implant bone resorption providing new clinical application for SIM in dental implant rehabilitation.